Legal Consequences of Marriage Agreement to Interested Third Parties - Rhesita Ayu Sophia Dewi; Herwastoeti; Dwi Ratna Indri Hapsari (Indonesia Law Reform Journal, 2023)
Marriage is a bond that forms a family within society and the state. With the existence of marriage can realize the welfare and happiness between humans. In a marriage, the husband or wife certainly brings assets called innate assets. So, before the marriage takes place, the prospective husband and wife make a marriage agreement which is a form of agreement made between one party and another and there is no coercion from any party. This study aims to find out how the process of making a marriage agreement deed and to find out whether the marriage agreement has legal consequences for third parties. The type of research used is empirical juridical with primary data and secondary data. Data collection techniques with interviews and observation. The results of the study show that in Law No. 1 of 1974 concerning Marriage, what is unanimously mixed are assets acquired during marriage. As for inherited assets, they remain under the authority of each unless mutually agreed upon by the husband and wife to be united in joint property. In the marriage agreement besides binding the husband and wife, the marriage agreement is also binding on third parties. So, this is a third party is very interested. Abstrak Perkawinan merupakan ikatan yang membentuk suatu keluarga di dalam lingkungan masyarakat dan negara. Dengan adanya perkawinan dapat mewujudkan kesejahteraan dan kebahagiaan antar manusia. Dalam suatu perkawinan suami atau istri tentunya membawa harta yang disebut harta bawaan. Maka sebelum perkawinan berlangsung para calon suami dan isteri membuat perjanjian perkawinan yang merupakan salah satu wujud dari perjanjian yang dibuat antara satu pihak dengan pihak yang lain dan tidak ada paksaan dari pihak manapun. Penelitian ini bertujuan untuk mengetahui bagaimana proses dalam pembuatan akta perjanjian perkawinan serta untuk mengetahui apakah perjanjian perkawinan memiliki akibat hukum bagi pihak ketiga. Jenis penelitian yang digunakan adalah yuridis empiris dengan data perimer dan data skunder. Teknik pengumpulan data dengan wawancara dan observasi. Hasil penelitian menunjukkan bahwa dalam Undang – Undang Nomor 1 Tahun 1974 tentang Perkawinan, yang dicampurkan secara bulat adalah harta yang diperoleh selama perkawinan. Sedangkan untuk harta bawaan tetap di bawah kekuasaan masing-masing kecuali disepakati bersama oleh suami dan istri untuk disatukan dalam harta bersama. Dalam perjanjian pernikahan selain mengikat pasangan suami-istri tersebut, perjanjian perkawinan juga mengikat terhadap pihak ketiga. Maka hal ini pihak ketiga sangat berkepentingan.